Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1128/aac.43.7.1609
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Locally Delivered Polyclonal Immunoglobulin against Pseudomonas aeruginosa Peritonitis in a Murine Model

Abstract: Infectious peritonitis results from bacterial contamination of the abdominal cavity. Conventional antibiotic treatment is complicated both by the emergence of antibiotic-resistant bacteria and by increased patient populations intrinsically at risk for nosocomial infections. To complement antibiotic therapies, the efficacy of direct, locally applied pooled human immunoglobulin G (IgG) was assessed in a murine model (strains CF-1, CD-1, and CFW) of peritonitis caused by intraperitoneal inoculations of 106 or 107… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Our IgG treatment schedule was chosen based on the fact that clearance rates for i.p. administered IgG in mice are rather rapid (∼3 h) [11–13].…”
Section: Resultsmentioning
confidence: 99%
“…Our IgG treatment schedule was chosen based on the fact that clearance rates for i.p. administered IgG in mice are rather rapid (∼3 h) [11–13].…”
Section: Resultsmentioning
confidence: 99%
“…High‐powered pulsatile lavage is superior to low‐pressure lavage, but causes more bone damage 28 . Most recently, the use of plasma proteins including specific immunoglobulins directed at decreasing bacterial adhesion molecules have had promising results 12–14,23–25 …”
Section: Discussionmentioning
confidence: 99%
“…The most common methods used are perioperative systemic antibiotics and intraoperative lavage with sterile fluids (often containing antimicrobials), but they do not eliminate infection in all situations 4 . In human and experimental orthopedics, several additives to lavage to increase bacterial removal and killing lavage have been investigated, including antimicrobials, soap, and immunoglobulins 12,20–25 . Our long‐term goal is to develop an ideal lavage solution that would be inexpensive, non‐toxic to tissues, and rapidly (<1 hour) bactericidal on all bone and tissue surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced, highly selective antibody doses could also exploit sophisticated delivery strategies21 to reduce initial pathogen adhesion, biofilm formation, and severity of infections. Recent work has shown that commercial human pooled polyclonal IgG injected intraperitoneally effectively protected mice against lethal peritonitis induced by virulent Pseudomonads 41. Infection survival was independent of either the mouse or Pseudomonas aeruginosa strain 41.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that commercial human pooled polyclonal IgG injected intraperitoneally effectively protected mice against lethal peritonitis induced by virulent Pseudomonads 41. Infection survival was independent of either the mouse or Pseudomonas aeruginosa strain 41. The timing of locally delivered polyclonal IgG was important for optimizing the survival benefit, with prophylactic local antibody applications producing the highest survival 41, 42…”
Section: Introductionmentioning
confidence: 99%